2023
DOI: 10.3390/ijms24032852
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Integrity Damage in Bacterial Meningitis: The Underlying Link, Mechanisms, and Therapeutic Targets

Abstract: Despite advances in supportive care and antimicrobial treatment, bacterial meningitis remains the most serious infection of the central nervous system (CNS) that poses a serious risk to life. This clinical dilemma is largely due to our insufficient knowledge of the pathology behind this disease. By controlling the entry of molecules into the CNS microenvironment, the blood–brain barrier (BBB), a highly selective cellular monolayer that is specific to the CNS’s microvasculature, regulates communication between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 145 publications
0
17
0
Order By: Relevance
“…In this study, we demonstrated that CXCL3 promotes microglia M1 polarization by binding to CXCR2, which ultimately induces the expression of pro-inflammatory cytokines (Figure 7). chemokines remain at high levels in the blood and brain for a long time [17,19]. In this study, we demonstrated that CXCL3 promotes microglia M1 polarization by binding to CXCR2, which ultimately induces the expression of pro-inflammatory cytokines (Figure 7).…”
Section: Discussionmentioning
confidence: 56%
“…In this study, we demonstrated that CXCL3 promotes microglia M1 polarization by binding to CXCR2, which ultimately induces the expression of pro-inflammatory cytokines (Figure 7). chemokines remain at high levels in the blood and brain for a long time [17,19]. In this study, we demonstrated that CXCL3 promotes microglia M1 polarization by binding to CXCR2, which ultimately induces the expression of pro-inflammatory cytokines (Figure 7).…”
Section: Discussionmentioning
confidence: 56%
“…In vitro and in vivo data showed that meningitic E. coli induced the upregulation of PDGFB, which dose-dependently increased BBB permeability by decreasing TJPs expression . A recent study found that meningitic E.…”
Section: Discussionmentioning
confidence: 98%
“…Intercellular junctions between BMECs play a critical role in maintaining vascular integrity and permeability for barrier functions . Several factors have been reported to contribute to BBB disruption in bacterial meningitis, including direct cellular damage caused by bacterial virulence factors (e.g., lipopolysaccharide, capsule, peptidoglycan, enolase, hyaluronidase, and hemolysin), as well as host-specific proteins [e.g., matrix metalloproteinases (MMP)-3, MMP-8, MMP-9, vascular endothelial growth factor A (VEGFA), and SNAI1] or proinflammatory cytokines [e.g., interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor (TNF)-α]. …”
mentioning
confidence: 99%
“…Several studies have found that E. coli strains containing all virulence genomes had a lower resistance phenotype than that observed in non-virulent E. coli strains, and this may be related to the regulation of the bacterial genome ( Čurová et al., 2020 ). As we know, meningitis-associated E. coli crosses the blood-brain barrier requiring a combination of virulence factors, such as OmpA , Ibe , CNF1 ( Yang et al., 2023 ). We therefore hypothesize that the reason why strains causing invasive infections were instead less resistant than those separated from sputum may be related to the complex regulation between virulence and drug resistance.…”
Section: Discussionmentioning
confidence: 99%